Activating peptides for cellular uptake via polymerization into high density brushes. Issue 2 (10th November 2015) - Blum, Angela P.; Kammeyer, Jacquelin K.; Gianneschi, Nathan C.
Abstract : The utility of peptide therapeutics is thwarted by an inability to enter cells, preventing access to crucial intracellular targets. Abstract : The utility of peptide therapeutics is thwarted by an inability to enter cells, preventing access to crucial intracellular targets. Herein, we describe a simple and potentially widely applicable solution involving the polymerization of a minimally modified amino acid sequence into a high density brush polymer. Specifically, non-cell penetrating peptides can be rendered competent for cell entry by first including a single Arg or Lys in their amino acid sequence, if one is not already present, along with a norbornenyl unit. This modified monomer is then polymerized by ring opening metathesis polymerization (ROMP). To demonstrate the utility of this strategy, a known therapeutic peptide, which does not penetrate cells on its own, was polymerized. The resulting polymer proficiently entered cells while maintaining its intracellular function. We anticipate that this methodology will find broad use in medicine, increasing or enabling the in vivo efficacy of promising peptide therapeutics.